FINANCIAL BEHAVIOUR OF INDIVIDUAL INVESTORS: A SEGMENTATION APPROACH - Sangeeta Arora AND Kanika Marwaha (Abhigyan, 2012)
The objective of the study is to identify the investor segments based on their attitudes and behavior in day to day financial matters and also to identify their socio-demographic characteristics. The study examines the individual’s financial competence and their consequential product needs. The survey is conducted in three districts of Punjab. Out of 120 questionnaires distributed, 100 were retained for final analysis. Cluster analysis identified three segments of investor’s i.e. rational, intuitive and conservative investors. Significant differences were found among the three segments in terms of their socio- demographic characteristics. The study provides implications for financial advisors who can offer more effective advice to the individual investors as per their needs and take into account the differences among different segments in order to help such segments improve their financial decisions.